The battle a new history of Waterloo - Barbero, Alessandro (Walker & Company, 2005)
At Waterloo, some 70,000 men under Napoleon and an equal number under Wellington faced one another in a titanic and bloody struggle. In the end, as John Keegan notes, contemporaries felt that Napoleon's defeat had "reversed the tide of European history." Even 190 years later, the name Waterloo resounds. Italian historian Alessandro Barbero's majestic new account stands apart from previous British and French histories by giving voice to all the nationalities that took part. Invoking the memories of British, French, and Prussian soldiers, Barbero meticulously re-creates the conflict as it unfolded, from General Reille's early afternoon assault on the chateau of Hougoumont, to the desperate last charge of Napoleon's Imperial Guard as evening settled in. From privates to generals, Barbero recounts individual miracles and tragedies, moments of courage and foolhardiness, skillfully blending them into the larger narrative of the battle's extraordinary ebb and flow. One is left with indelible images: cavalry charges against soldiers formed in squares; the hand-to-hand combat around farmhouses; endless cannon balls and smoke. And, finally, a powerful appreciation of the inevitability and futility of war.